ChemInform Abstract: Highly Efficient Low Melting Mixture Catalyzed Synthesis of 1, 8‐Dioxo‐dodecahydroxanthene Derivatives. Issue 46 (24th October 2013) - Li, Peihe; Ma, Feiping; Wang, Ping; Zhang, Zhanhui
Abstract This method uses a citric acid/dimethylurea melt as an easily recoverable reaction medium which can be reused at least five times without a significant loss in activity.